2009
DOI: 10.1080/08820130902888383
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging on Antioxidant Response and Phagocytosis in Senescent Erythrocytes

Abstract: Red blood cell (RBC) aging is a complex process affected by immunological and biochemical parameters. In this work we studied the antioxidant response in RBC of different ages. We also investigated their interaction with peripheral blood monocytes. Anticoagulated blood samples from 19 O RhD+ volunteers' donors were processed. Young (Y) RBC and Senescent (Se) RBC were obtained by self-formed gradients of Percoll. The fractionation of the erythrocytes suspensions was demonstrated by statistically significant den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
6
1
Order By: Relevance
“…Previous studies, using Percoll‐fractionated RBCs, have shown that denser RBCs are more susceptible to phagocytosis . In contrast, our results did not show a significant difference in erythrophagocytosis between density fractionated young and old stored RBCs (Fig.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Previous studies, using Percoll‐fractionated RBCs, have shown that denser RBCs are more susceptible to phagocytosis . In contrast, our results did not show a significant difference in erythrophagocytosis between density fractionated young and old stored RBCs (Fig.…”
Section: Discussioncontrasting
confidence: 88%
“…). Targeting of RBCs for phagocytosis in vivo is complex and involves a number of different mechanisms that may contribute to the increased erythrophagocytosis observed in this study. We have previously shown that detection of RBC membrane sialylation using lectins decreases over the storage period .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, only a fraction of circulating erythrocytes appear to be sensitive to those challenges. The susceptibility may be influenced by erythrocyte age, as senescent erythrocytes may have a decreased capacity to counteract oxidative stress [45][46][47]. On the other hand, newly formed erythrocytes may by particularly vulnerable, as shown following return from high altitude or a space flight [48] or in patients with paroxysmal nocturnal hemoglobinuria and myelodysplastic syndrome [49].…”
Section: Discussionmentioning
confidence: 99%
“…Normal rat erythrocytes have a life span of 90 days, during which period cells senesce and are phagocytosed by macrophages. A normal senescent erythrocyte is identified by reduced activities of enzymes such as glucose-6-phosphate dehydrogenase and membrane-bound b5R (b5Rm) that are indicators of reduced antioxidant responses accompanying aging of erythrocytes (Brajovich et al 2009). However, under certain conditions, accelerated clearance of erythrocytes from circulation may occur with the problem being magnified by the low resistance of young erythrocytes towards various challenges Effect of peroxyl radical-mediated changes on intracellular calcium and in the presence and absence of vitamin C in young and old erythrocytes.…”
Section: Discussionmentioning
confidence: 99%